2008
DOI: 10.1111/j.1398-9995.2008.01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality‐of‐life and asthma‐severity in general population asthmatics: results of the ECRHS II study

Abstract: In population-based asthmatics, the specific AQLQ questionnaire, and also to a lesser extent the generic SF-36 questionnaire, were sensitive to asthma-severity. Frequencies of asthma attacks, of nocturnal symptoms and hospitalization for asthma have independent impact on HRQL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 32 publications
8
67
0
Order By: Relevance
“…The AQLQ score in participants with asthma and no insomnia were similar to the score found in a population-based study of 864 adults with asthma. 33 The presence of insomnia in patients with asthma may lead to more severe depression and anxiety symptoms and further reductions in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The AQLQ score in participants with asthma and no insomnia were similar to the score found in a population-based study of 864 adults with asthma. 33 The presence of insomnia in patients with asthma may lead to more severe depression and anxiety symptoms and further reductions in quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that HRQoL in asthma is correlated with asthma severity to some extent [21,22]. Nevertheless, differences in HRQoL in asthma cannot be fully explained by asthma severity or any of the other traditional treatment outcome measures, which is why this measure is interesting: it captures some aspects of treatment outcome that cannot otherwise be measured.…”
Section: Discussionmentioning
confidence: 99%
“…An important goal of asthma management strategies is to improve health-related quality of life (25,26). The AQLQ is a validated tool for assessing the impact of asthma and evaluating outcomes of various therapies (27).…”
Section: Discussionmentioning
confidence: 99%